The city of refuge the collected stories of Rudolph Fisher - Fisher, Rudolph, 1897-1934 (University of Missouri Press, 2008)
"Harlem Renaissance tales that deal with the problems faced by newcomers to Harlem, ancestor figures who struggle to instill a sense of integrity in the young, problems of violence and vengeance, and tensions of caste and class. This version is expanded to include seven previously unpublished stories"--Provided by publisher.